Children's understanding of mixed emotions in self and other: Verbal reports and visual representations. Issue 3 (7th December 2017) - Burkitt, Esther; Lowry, Ruth; Fotheringham, Francesca
Abstract: Patterns of simultaneous experiences of mixed emotion have been found in adulthood using analogue emotion scales (AES) that measure subjective intensity and duration of two emotions in one graph. Children report simultaneous emotions increasingly between 5 and 7 years of age. These reports may underestimate the type of simultaneous experiences. This research piloted an extended interview and AES to assess subjective mixed emotion types in childhood. One hundred and eighty children (91 girls, 89 boys) between 5 years 2 months and 7 years 3 months ( M  = 6 years 3 months) were allocated to two conditions (self: n  = 90, other: n  = 90), hearing a vignette describing a mixed emotion event occurring either to another child or to themselves. Log‐linear analysis of reported and graphed responses showed simple, sequential, prevalence, inverse, and highly simultaneous emotion experiences. Younger children reported more single and sequential experiences. Older children reported and graphed more simultaneous experiences. Mixed emotion varied by measure type with more prevalence experiences graphed than reported and more inverse experiences reported than graphed. The results indicate the potential for the utility of the adapted AES for use with children. Highlights: Investigating types of mixed emotion experiences in childhood using reports and an adapted analogue emotion scale. Children reported and graphed single and mixed emotion experiences for themselves or another child. Single, sequential, prevalence, inverse, and highly simultaneous experiences were reported and graphed by both age groups in both conditions. More prevalence experiences were graphed than reported and more inverse experiences reported than graphed. Simultaneous patterns of mixed emotion could extend models of emotion recognition in childhood and could supplement interview and assessment procedures.